1975
DOI: 10.1530/jrf.0.0450415
|View full text |Cite
|
Sign up to set email alerts
|

Boar Seminal Zinc-Precipitable Protein and the Haemagglutinin

Abstract: About 30% of boar seminal plasma nitrogen is maximally precipitated at room temperature by 6 to 10 mm zinc in citrate solution at pH 8. A rise in the total nitrogen precipitated by 1 to 6 mm zinc is accompanied by a fall in the haemagglutinin titre of the supernatant fluid. At 6 mm zinc addition, 95% of the haemagglutinin is precipitated, but much of this is recoverable by resolution of the zinc precipitate. Protein profile studies by gel-filtration chromatography of the zinc precipitate solution reveals a mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1978
1978
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…3k). These findings are in accordance with those of a previous study indicating that boar vesicular glands might play a key role in the secretion of ZnBPs to the seminal plasma (Boursnell et al, 1975. In bulls, significant amounts of ZnBPs have been detected in the cauda epididymidis and vas deferens (Henkel et al, 2003), whereas in the dog the prostate seems to contribute the bulk of the ZnBPs to the seminal plasma (Mogielnicka-Brzozowska et al, 2012).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…3k). These findings are in accordance with those of a previous study indicating that boar vesicular glands might play a key role in the secretion of ZnBPs to the seminal plasma (Boursnell et al, 1975. In bulls, significant amounts of ZnBPs have been detected in the cauda epididymidis and vas deferens (Henkel et al, 2003), whereas in the dog the prostate seems to contribute the bulk of the ZnBPs to the seminal plasma (Mogielnicka-Brzozowska et al, 2012).…”
Section: Resultssupporting
confidence: 92%
“…Using affinity chromatography and electrophoretic techniques, ZnBPs have been isolated and characterized from canine and boar seminal plasma (Mogielnicka-Brzozowska et al, 2011, Mogielnicka-Brzozowska et al, 2012. In the boar ZnBPs have been shown to possess antibacterial, antioxidant and immunomodulating properties , Boursnell et al, 1975, and improved sperm motility and acrosome integrity, when added to extended semen stored at 4ºC (Mogielnicka-Brzozowska et al, 2011). In the literature, the source of ZnBPs of boar seminal plasma has not been clearly defined as yet.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence has been shown that zinc ions, secreted by the prostate and vesicular glands, bind to different proteins ligands, which are implicated in sperm-egg fertilization processes in the female reproductive tract (Boursnell et al 1975, Arver 1982, Hołody and Strzeżek 1999, Siciliano et al 2000, Mogielnicka-Brzozowska et al 2011. Zinc-binding proteins (ZnBPs) have been identified in the seminal plasma of human (Arver 1982, Arver and Eliasson 1982, Siciliano et al 2000 and boar (Boursnell et al 1975, Strzeżek et al 1987, Hołody and Strzeżek 1999, Mogielnicka-Brzozowska et al 2011. Evidence has been shown that most of the zinc in human and canine seminal plasma originates in the prostate (Johnson et al 1969, Lindholmer andGlaumann 1972).…”
Section: Introductionmentioning
confidence: 99%
“…The possible involvement of the cationic haemagglutinin present in boar seminal plasma (Boursnell, 1967;Boursnell & Briggs, 1969) was also explored, particularly as it appeared to be capable of binding zinc (Boursnell, Noble & Andrews, 1975). A potent colourless and neutral polyanionic reagent, Antrypol, was used to remove completely the haemagglutinin from the seminal plasma.…”
Section: Introductionmentioning
confidence: 99%